Attitudes towards General Practice: a comparative cross-sectional survey of 1(st) and 5(th) year medical students - Kruschinski, Carsten (German Medical Science GMS Publishing House, 2012)
Objective: Positive attitudes towards General Practice can be understood as a prerequisite for becoming a General Practitioner (GP) and for collaboration with GPs later on. This study aimed to assess attitudes of medical students at the beginning and the end of medical school. Methods: A total of 160 1(st) year students at Hannover Medical School were surveyed. Their attitudes were compared to those of 287 5(th) year students. Descriptive, bi- and multivariate analyses were performed to investigate influences of year of study and gender. Results: Year of study and gender both were associated with the attitudes towards General Practice. The interest in General Practice and patient-orientation (communication, care of older patients with chronic diseases) was higher in 1(st) year students compared to more advanced students. Female students valued such requirements more than male students, the differences in attitudes between the years of study being more pronounced in male students. Conclusion: Despite some limitations caused by the cross-sectional design, the attitudes towards General Practice competencies changed to their disadvantage during medical school. This suggests a formative influence of the strategies used in medical education. Educational strategies, however, could be used to bring about a change of attitudes in the other direction.